Wybrane aspekty prywatyzacji zarządzania nieruchomościami komunalnymi - Wartalska, Magdalena (Selected Aspects of Privatization of Communal Real Estate, 2007)
The subject of this article is dedicated to constantly current objective of privatization of communal real estate. The importance of discussed issue is related to introducing new market resolutions in the process of managing properties, which will have a consequence in increasing efficiency and sustainability of used and owned resources by territorial self-government. The requirement of rational usage of communal resources, including postulated disconnection of owner and manager functions, more often leads to actions resulting in privatization of communal real estate. Meaning here, that there is a change in the ownership structure of managing subjects in favour of private ownership with simultaneous reduction of involvement from commune in direct management services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 623-633